"Branca de neve e os sete anões", "espelho, espelho meu" : uma análise discursiva - Andrade, Glícia Kelline Santos (2015)
The present work consists in a discursive approach of our master’s degree dissertation’s Project object: the fairy tale “Snow White And The Seven Dwarfs”, the movie “Mirror Mirror”; two distinct materialities: the first essencially linguistic; the second, filmic, presenting verbal and non-verbal language. Our aim is, initially, proceed to a comparison between these two versions, establishing the relations of comparison/contrast, analyzing them discursively. As they are two distinct materialities, we consider the question regarding the discursive gender: the written short story, the movie. As a theoretical contribution to the gender study, we took into consideration the contributions from Bakhtin (1997), to whom the genders are relatively stable types of enunciation. Despite this contribution, this work is confined to the Archaeological Discourse Analysis and, as such, is based mostly on Foucault postulates. According to Revel (2005, p. 13), “The foucaultian Archaeological Method” seeks to, [...], rebuilt behind the fact a whole network of speeches, of powers, of strategies and of practices”. Through the light of Focault’s postulates (2008, 2009, 2012a; 2012b), we have observed, initially, the authorship question, the woman´s position, in both materialities, the relations of power/knowledge, the enunciation, the speech, the already-said speeches. We have yet reflected about the body usage during the process of disciplinarization, linked to the relation power-knowledge, to the punishment; the update of the speech over the social place where the characters enunciate themselves (whether they got social prestige or not). We have analyzed the cultural industry (TEIXEIRA COELHO), specially the one from the cinematographic media (BERNARDET; KRISTEVA), in the update process of the ideal of hapiness, the reiteration of marriage, as a social insititution founder of this happiness. This discourse is built through the use of a values’ system, permeated by the “existence of a happy ending”, due to the ability to reach out a social status of prestige (related to royalty). We highlight also the control of behavior patterns (obedience versus disobedience), these being determinant when it comes to the constitution of a social subject. As a result, we have understood that the cinematographic media allows the spreading of these values/discourses, in an attempt to preserve them and, as they are doing so, they also open dialogues with the religious discourse and the pedagogical. Once given our object of study and the theory sustaining it, we consider this research with a qualitative character. We judge the relevance of this present because it allows a reflection over the pointed out aspects.